2007
DOI: 10.1002/bjs.5911
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the long-term cost-effectiveness of endovascular or open repair for abdominal aortic aneurysm

Abstract: EVAR is unlikely to be cost-effective on the basis of existing devices, costs and evidence, but there remains considerable uncertainty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
69
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 17 publications
1
69
0
Order By: Relevance
“…However, the short time horizon in the analysis may be biased, as it assumes no difference in survival (or costs) beyond 1 year. The EVAR model (2008) 200 was a lifetime analysis extrapolating from the 4-year results of EVAR trial 1. This study concluded that EVAR was unlikely to be cost-effective, given the assumptions that patients faced a continuing elevated risk (compared with open repair) of late AAA mortality and reinterventions after EVAR for the rest of their lives and that there was no difference in overall survival after 4 years.…”
Section: 208mentioning
confidence: 99%
See 3 more Smart Citations
“…However, the short time horizon in the analysis may be biased, as it assumes no difference in survival (or costs) beyond 1 year. The EVAR model (2008) 200 was a lifetime analysis extrapolating from the 4-year results of EVAR trial 1. This study concluded that EVAR was unlikely to be cost-effective, given the assumptions that patients faced a continuing elevated risk (compared with open repair) of late AAA mortality and reinterventions after EVAR for the rest of their lives and that there was no difference in overall survival after 4 years.…”
Section: 208mentioning
confidence: 99%
“…There have been a number of recent published economic evaluations of these treatments. This chapter reviews the methods and data used in those studies, highlights the key uncertainties about the cost-effectiveness of the treatments, and updates a previously published decision model 200 in the light of the recently available mid-and long-term results of the relevant clinical trials: the EVAR trial 1, 201 the DREAM 160 and the OVER trials. 165 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In their model, conversion from OSR to EVAR was not included as it is unlikely and the EVAR 1 trial showed that none of the OSR patients were converted. 45 Furthermore, mortality (all-cause and aneurysm related) and complications during the first 30 days need to be incorporated in the short-term model, if a difference between interventions exists. Complications can be categorised into four types: cardiac complications [e.g.…”
Section: Short-term Model (Fit For Open Surgical Repair)mentioning
confidence: 99%